Carrier Status of Methicillin-Resistant Staphylococcus Aureus (MRSA) - Amna Tariq , Shireen Rafiq , Azad Ali Azad , Sophia Khan , Nauzhat Nauman, Amna Tariq , Shireen Rafiq , Azad Ali Azad , Sophia Khan , Nauzhat Nauman (Journal of Rawalpindi Medical College, 2017)
To investigate nasal carriage of Methicillin-Resistant Staphylococcus aureus (MRSA) among dental healthcare workers (HCWs) , as the carriers could be the potential risk factor for the transmission of nosocomial infection when exposed to hospital setting during clinical posting. Methods: One hundred HCWs including postgraduate trainees, house physicians, staff nurses and technicians participated in the study. Nasal specimens were obtained by using cotton swabs moistened in sterile saline. The nasal specimens collected were processed as per (CLSI, 2008). Specimens were inoculated on blood agar to look for β-hemolysis of Staphylococcus aureus. Nutrient agar was used for the direct colony identification of Staphylococcus aureus. Mannitol salt agar (MSA) and DNAse were used as selective media for the isolation of Staphylococcus aureus and incubated at 35˚C for 48 hrs.Resistance to methicillin was detected with cefoxitin(30 μg) through Disk Diffusion Test and interpreted according to (CLSI, 2009). A diameter of ≥22 mm was considered as susceptible and ≤21 mm as resistant as per (CLSI, 2010). Results: Out of 100 nasal swabs collected, 71 nasal swabs were from the dental surgeons and 29 were from the nursing staff, 35 (35%) showed a growth of Staphylococcus aureus. Among those who were positive for Staphylococcus aureus 62.85%were positive for MRSA. Overall 22 (22%) out of a 100 individuals came out to be positive for MRSA. Conclusion: Health care workers (HCWs) were the potential colonizers of methicillin resistant Staphylococcus aureus and may serve as reservoirs or disseminators of MRSA.